2014
DOI: 10.1002/stem.1595
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically Active Human Brown Adipose Tissue Derived Stem Cells

Abstract: Brown adipose tissue (BAT) plays a key role in the evolutionarily conserved mechanisms underlying energy homeostasis in mammals. It is characterized by fat vacuoles 5-10 mm in diameter and expression of uncoupling protein one, central to the regulation of thermogenesis. In the human newborn, BAT depots are typically grouped around the vasculature and solid organs. These depots maintain body temperature during cold exposure by warming the blood before its distribution to the periphery. They also ensure an optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 34 publications
(45 reference statements)
1
52
0
6
Order By: Relevance
“…In the present study, we induced T2DM in a rat model by a high-fat diet combined with STZ administration and performed ASC infusion at the 28 th day after STZ injection. We found that ASC infusion could effectively ameliorate hyperglycemia in T2DM rats, which was consistent with other reports [1,2,23]. Furthermore, our results of hyperinsulinemic-euglycemic clamp studies demon-INSR in skeletal muscle and adipose and liver tissues after therapy to investigate the possible mechanisms involved in the effect of ASC infusion on insulin sensitivity.…”
Section: A B Csupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, we induced T2DM in a rat model by a high-fat diet combined with STZ administration and performed ASC infusion at the 28 th day after STZ injection. We found that ASC infusion could effectively ameliorate hyperglycemia in T2DM rats, which was consistent with other reports [1,2,23]. Furthermore, our results of hyperinsulinemic-euglycemic clamp studies demon-INSR in skeletal muscle and adipose and liver tissues after therapy to investigate the possible mechanisms involved in the effect of ASC infusion on insulin sensitivity.…”
Section: A B Csupporting
confidence: 91%
“…ASC can be isolated from small amounts of adipose tissue, efficiently expanded to achieve a very large number after 3 to 4 passages, and have the advantage of low immunogenicity and high multipotency. Their immunmodulatory function, homing and migratory patterns, as well as previous clinical trials, have suggested that these cells are efficient and safe for treating several classes of autoimmune diseases [1][2][3][4].…”
mentioning
confidence: 95%
“…Recently, a role for alternatively activated macrophages and eosinophils in the development of functional beige BAT has been reported in mice (57,58). Additionally, a population of brown adipocyte progenitors was identified in skeletal muscle in both mice (59) and humans (60,61). These cells could be differentiated into mature brown adipocytes by stimulation with bone morphogenetic protein (BMP) 7, thus presenting a potential target for pharmacological intervention in humans.…”
Section: (Re)discovery Of Bat In Human Adultsmentioning
confidence: 99%
“…On the other hand, specific origins of ADSC may also be taken into account for special therapeutic needs. For instance, a clonogenic population of metabolically active stem cells has been reported to reside in adult human brown adipose tissue that may be activated to participate in energy homeostasis in vivo and, therefore, may be of therapeutic importance for obesity and related metabolic disorders (Silva et al 2014).…”
Section: Source-and Donor-dependent Variability In Adsc Qualitymentioning
confidence: 99%